The Yin-Yang of myeloid cells in the leukemic microenvironment: Immunological role and clinical implications - Magalhães-Gama, Fábio; Alves-Hanna, Fabíola Silva; Araújo, Nilberto Dias; Barros, Mateus Souza; Silva, Flavio Souza; Catão, Claudio Lucas Santos; Moraes, Júlia Santos; Freitas, Izabela Cabral; Tarragô, Andréa Monteiro; Malheiro, Adriana; Teixeira-Carvalho, Andréa; Costa, Allyson Guimarães (Frontiers in Immunology, 2022)
The leukemic microenvironment has a high diversity of immune cells that are phenotypically and functionally distinct. However, our understanding of the biology, immunology, and clinical implications underlying these cells remains poorly investigated. Among the resident immune cells that can infiltrate the leukemic microenvironment are myeloid cells, which correspond to a heterogeneous cell group of the innate immune system. They encompass populations of neutrophils, macrophages, and myeloid-derived suppressor cells (MDSCs). These cells can be abundant in different tissues and, in the leukemic microenvironment, are associated with the clinical outcome of the patient, acting dichotomously to contribute to leukemic progression or stimulate antitumor immune responses. In this review, we detail the current evidence and the many mechanisms that indicate that the activation of different myeloid cell populations may contribute to immunosuppression, survival, or metastatic dissemination, as well as in immunosurveillance and stimulation of specific cytotoxic responses. Furthermore, we broadly discuss the interactions of tumor-associated neutrophils and macrophages (TANs and TAMs, respectively) and MDSCs in the leukemic microenvironment. Finally, we provide new perspectives on the potential of myeloid cell subpopulations as predictive biomarkers of therapeutical response, as well as potential targets in the chemoimmunotherapy of leukemias due to their dual Yin-Yang roles in leukemia.